Pemberian Pupuk Anorganik dan Pemangkasan Daun Terhadap Pertumbuhan dan Produksi Jagung Varietas Pioneer-23 - Sthefani Melkasari; Sabar Ginting; Irsal Irsal (Universitas Sumatera Utara, 2015)
This research aims to get a right dose of inorganic fertilizer and the appropriate amount of leaf pruning on the growth and yield of maize (Zea mays L.) varieties Pioneer - 23, conducted in community land Jl. Setia Budi, Simpang Selayang village, subdistrict of Medan Tuntungan with ± 25 m altitude above sea level in March and July 2011 using a randomized block design factorial with 2 factors: inorganic fertilizer (NPK) (0, 175, 350, dan 525 kg/ha) and pruning leaves (not pruned, 2 lowest leaves pruned, and 4 lowest leaves pruned). The results showed that inorganic fertilizer was significant effected for plant height of 6 WAP, days to flowering, amount of leaf chlorophyll, plant dry weight’s sampels, plot’s production, weight of dry shelled sampels, weight of 100 grains seeds. Leaves pruning was notsignificant effected for all parameters except days to flowering and amount of leaf chlorophyll The interaction of inorganic fertilizer with pruning leaves show were notsignificant effected for all parameters.Keywords : maize, inorganic fertilizer, leaves pruning